Effect of a novel healthcare leadership program on leadership and emotional intelligence. Issue 5 (September 2021) - Bonazza, Nicholas A.; Cabell, Grant H.; Cheah, Jonathan W.; Taylor, Dean C.
The purpose of this study was to assess the effectiveness of the Feagin Leadership Program (FLP) in teaching leadership domains and emotional intelligence. An anonymous survey of 178 graduates of FLP (2011–2019) including the Trait Emotional Intelligence Questionnaire-Short Form (TEIQue-SF) was used to assess emotional intelligence and program views. ANOVA was used to compare the difference in emotional intelligence domains between groups. Respondents reported the FLP most improved skills in communication, emotional intelligence, and team building. Medical students (18, 38.3%) and faculty/staff (5/14, 35.7%) reported the most relevant domain was emotional intelligence; residents/fellows reported the most relevant domain was teamwork (8/37, 21.6%). Respondents in residency/fellowship had the highest score in emotionality (P = .01). These results suggest that a healthcare leadership program tailored to medical trainees was effective in improving their competency in various leadership domains, and that emotional intelligence and teamwork were the most relevant components of the program.